Phonological and Lexical Change in Kudangan: Implications for Mother-Tongue-Based Education in Central Kalimantan - Qalyubi, Imam; Widiastuty, Hesty; Adlina, Fadiah; Misrita, Misrita (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
This study examines phonological and lexical change in Kudangan, a minority language spoken by the Dayak Tomun community in Central Kalimantan, and explores its implications for mother-tongue-based regional language education. Employing a qualitative linguistic approach, data were collected through purposive sampling involving community elders and fluent speakers, semi-structured interviews, participant observation, and lexical elicitation. Phonological analysis was conducted using segmental comparison and rule-based description, while lexical change was analyzed in terms of morphological restructuring and semantic shift. The findings reveal systematic sound correspondences, including vowel modification (e.g., /air/ → /arai/) and final consonant addition (e.g., /hujan/ → /hujant/), alongside patterned lexical variation reflecting sociocultural meaning and language contact. These results demonstrate that Kudangan maintains an internally coherent phonological and lexical system despite pressure from dominant languages. The study offers novel empirical documentation of an under-described Austronesian variety and provides a linguistic foundation for developing culturally responsive teaching materials and sustaining minority language transmission. Accordingly, phonological and lexical description is positioned not only as documentation but also as a strategic resource for regional language education and long-term language maintenance.